THEORETICAL BASIS FOR SYNERGETICS OF ECONOMIC PROCESSES - V.V. Yakimtsov (European Scientific Journal, ESJ, 2014)
The article presents theoretical basis for the application of synergetic approaches in the economy. The meaning and essence of the concept of “synergetics” are given. The essence of synergetic approach to understanding processes in the economy and natural sciences is determined. The use of synergetic methodology for creating the nonlinear cognitive model is grounded. The development prospects of synergetic approaches for their use in the research of economic processes and recovery from the crisis state are presented.